2018
DOI: 10.1002/jaba.526
|View full text |Cite
|
Sign up to set email alerts
|

Abstraction of tactile properties by individuals with autism and Down syndrome using a picture‐based communication system

Abstract: The present study evaluated the efficacy of a set of procedures for bringing tact extensions of abstract tactile properties under stimulus control. Two participants with disabilities who communicated via a picture-based communication system received reinforcement for tacts of tactile properties of four wet/dry and four hard/soft stimuli. Test trials were conducted to evaluate the extent to which the participants' correct responding generalized to novel stimuli with the same tactile properties. The results sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…The results are consistent with Belisle et al (2018) who used MET to teach individuals with ASD and Down syndrome to tact abstract tactile stimuli: wet, dry, hard, and soft. The current study similarly incorporated MET; two different objects produced each sensation during training, and two novel objects produced each sensation during novel‐object generalization probes.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The results are consistent with Belisle et al (2018) who used MET to teach individuals with ASD and Down syndrome to tact abstract tactile stimuli: wet, dry, hard, and soft. The current study similarly incorporated MET; two different objects produced each sensation during training, and two novel objects produced each sensation during novel‐object generalization probes.…”
Section: Discussionsupporting
confidence: 90%
“…The target body parts, sensations, and stimulating objects are shown in Table 1 and were counterbalanced across participants. The target arrangement involved MET, as suggested by previous recommendations and research (Belisle et al, 2018; Sprague & Horner, 1984; Stokes & Baer, 1977).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both studies may have produced weak stimulus control because (a) each stimulus property was paired with a single object rather than with multiple objects, and (b) nonvisual properties, such as soft, cannot be acquired without relevant sensory experiences. Belisle et al (2019) used the tactile sensory modality (i.e., touching and feeling an item hidden in a box) to effectively teach the stimulus properties of wet/dry and soft/hard to individuals with ASD and developmental delays. The results demonstrated that using relevant sensory experiences is an effective tool for establishing stimulus control of stimulus properties.…”
mentioning
confidence: 99%